Estimation of Biomass Storage and Net Primary Productivity of Five Dominant Forests of Kumaun Himalaya along the Altitudinal Gradient - Gahlot, Tanuja; Kushwaha, Arun Kumar; Gwal, Pratibha; Joshi, Prachi; Rawat, Y. S.; Rawat, P. S. (Indian Forester, 2023)
The present study was performed in the forest of Kumaun Himalaya present along the altitude as to determine the biomass storage and NPP of the forests. For this purpose, a total of 150 plots were placed at 15 different sites by following plot sampling method. Allometric regression equations were used for the calculation of tree biomass and NPP, which were previously developed for the similar forests and similar tree species of Himalaya by different workers. The biomass value of all the five forests ranged from 156-918.36 t ha-1 and NPP varied between 10.70 and 20.30 t ha-1 yr-1. Low biomass value was reported at middle altitude (chir-pine and banj-oak forest) and lowest altitude (teak forest) as compared to the high altitude forests. However, all the forests showed high net primary productivity. The regression analysis showed a positive correlation of biomass with NPP (r2 =0.595). No relationship was seen between altitude and biomass and altitude and net primary productivity. In fact the entire elevation range supports good productivity and biomass. It was also noticed that expansion of chir-pine forests towards the banj-oak forest was responsible for the low biomass of banj-oak forests. Banj-oak forests at this elevation are considered to be the soil binder forests which bind the soil and stop landslides. However the chir-pine expansion in banj-oak forest area is facing tremendous loss in its forest vegetation.